The Indo-Pacific and Southeast Asia: the impact of external strategies on Southeast Asia and ASEAN’s response - Gracia Abad Quintanal (Revista UNISCI, 2022)
The Indo-Pacific concept is imprecise and designates more a geopolitical reality than a geographical space, but it is not, as is often suggested, a recent creation of the US, nor of the Trump administration. On the contrary, several actors have used it before the United States itself. And the US will not be the last actor to adopt it, either. On the contrary, it has gradually been adopted by other actors, including ASEAN, which tries to turn the concept in its favour in a way that reaffirms the importance of the group in the region as a whole and does not put in question neither “its centrality or its unity”, something that is far from being achieved.